2015
DOI: 10.1186/s12885-015-1271-4
|View full text |Cite
|
Sign up to set email alerts
|

High expression of NQO1 is associated with poor prognosis in serous ovarian carcinoma

Abstract: BackgroundNAD(P)H:quinone oxidoreductase (NQO1) is a flavoprotein that catalyzes two-electron reduction and detoxification of quinones and its derivatives. NQO1 catalyzes reactions that have a protective effect against redox cycling, oxidative stress and neoplasia. High expression of NQO1 is associated with many solid tumors including those affecting the colon, breast and pancreas; however, its role in the progression of ovarian carcinoma is largely undefined. This study aimed to investigate the clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…NQO1 is generally recognized as a 'cell protector', its induction in response to various noxious stimuli provides protection for cells against oxidative damage and oxidative stress-associated pathological conditions including cancer (9,10). Conversely, an increasing number of studies revealed abnormal increases in NQO1 expression levels in solid tumors of the adrenal gland, breast, colon, lung, ovary, pancreas, thyroid, skin and bladder (9)(10)(11)(12)(13)(14)(15)(16). High-level expression of NQO1 may be associated with cancer progression and it was suggested to be a poor prognostic marker of these types of cancer (14,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NQO1 is generally recognized as a 'cell protector', its induction in response to various noxious stimuli provides protection for cells against oxidative damage and oxidative stress-associated pathological conditions including cancer (9,10). Conversely, an increasing number of studies revealed abnormal increases in NQO1 expression levels in solid tumors of the adrenal gland, breast, colon, lung, ovary, pancreas, thyroid, skin and bladder (9)(10)(11)(12)(13)(14)(15)(16). High-level expression of NQO1 may be associated with cancer progression and it was suggested to be a poor prognostic marker of these types of cancer (14,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, an increasing number of studies revealed abnormal increases in NQO1 expression levels in solid tumors of the adrenal gland, breast, colon, lung, ovary, pancreas, thyroid, skin and bladder (9)(10)(11)(12)(13)(14)(15)(16). High-level expression of NQO1 may be associated with cancer progression and it was suggested to be a poor prognostic marker of these types of cancer (14,16,17). Upregulation of NQO1 during carcinogenesis may provide cancer cells with a growth advantage and protection against extreme oxidative stress environments (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…PV9000; ZSGB-Bio, Beijing, China) at RT for 30 min, the slides were incubated with streptavidin-peroxidase complex at RT for 30 min. Immunostaining was developed using 3,3'-diaminobenzidine, and Mayer's hematoxylin was used for counterstaining (20). Rabbit immunoglobulin G (IgG) (1:2,500 dilution; catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a predicted target of the under-expressed miR-148, NQO1 gene, was found to have a large number of interactions and to be up-regulated in CCA. NQO1 over-expression occurs in different tumors compared to their normal surrounding tissues [62] and was recently associated with poor prognosis in serous ovarian cancer [63]. Cholangiocarcinoma is highly resistant to chemotherapy and NQO1 protein, NAD(P)H-quinone oxidoreductase 1, has been shown to play a cooperative role in cancer chemoresistance [64].…”
Section: Figurementioning
confidence: 99%